Lifespan mercury accumulation pattern in Liza aurata: evidence from two southern European estuaries - Tavares, S. (2019)
Mercury accumulation throughout the lifespan of Liza aurata (Risso, 1810) was analysed in four tissues (muscle, gills, liver and brain) in two southern European coastal ecosystems with distinct mercury contamination. Specimens from four to five age classes were captured in two sampling sites in the Ria de Aveiro (Laranjo bay and Mira), a system historically contaminated by industrial mercury, and in one site in the Mondego estuary, assumed as a mercury-free ecosystem. Mercury concentration in all tissues was found to be significantly higher in the Ria de Aveiro (Laranjo bay) compared to the Mondego, in accordance with the environmental contamination (water, sediments and suspended particulate matter). Significant differences inside the Ria de Aveiro (between the Mira and Laranjo bay) were only detected in the liver. This tissue registered the highest levels of mercury (ranging from 0.11 to 4.2 μg g−1) in all sampling sites, followed by muscle, brain, and gills. In all sampling sites and tissues was denoted a mercury dilution pattern along the lifecycle (except in liver at the Mondego, the reference area where the concentrations are always very low). An exponential trend was found in the metal age variation patterns in Laranjo (the most contaminated area) and a linear trend in the Mira and the Mondego (the least contaminated areas). Organic mercury concentration in muscle generally accounted for over 95% of total mercury concentration, and followed the same accumulation pattern of total mercury. This fish species is of lesser importance in mercury transfer to adjacent coastal areas and although the consumption of fish from Laranjo may present some risk for the humans, this risk decreases with fish age/size.